Fertility-Sparing Treatment in Young Patients With Grade 2 Presumed Stage IA Endometrioid Endometrial Adenocarcinoma - Yu, Mei; Wang, Yao; Yuan, Zhen; Zong, Xuan; Huo, Xiao; Cao, Dong-yan; Yang, Jia-xin; Shen, Keng (Frontiers in Oncology, 2020)
Purpose: To assess the efficacy of fertility-sparing treatment for young women with grade 2 presumed stage IA endometrioid endometrial adenocarcinoma (EEA) . Methods: We retrospectively reviewed the medical records of 8 patients with grade 2 presumed stage IA endometrioid endometrial adenocarcinoma who had received fertility-sparing treatment in Peking Union Medical College Hospital between 2011 and 2018. Results: The median age of patients was 26 years (range, 22-35 years). Complete response (CR) was found in 7 of the 8 cases. The median time to response was 3 months (range, 3-9 months). Of the complete responders, 3 of 7 had recurrence and were treated with second-line fertility-sparing therapy. Two of the 3 recurrent patients achieved CR and 1 patient subsequently conceived. Pregnancies and successful deliveries were achieved in 2 of 4 patients. The average follow-up period was 31 months (range, 21-77 months). Conclusions: Fertility-sparing therapy is a feasible treatment option in patients with presumed stage IA, grade 2 endometrial cancer. Although our results are encouraging, they are based on very limited numbers and patients should be informed the risk of tumor progression during treatment. Further evaluations are still required before recommending fertility-sparing therapy to endometrial cancer patients with more advanced disease in routine practice.